Odpowiedź :
Odpowiedź:
a) u(x)-w(x) = ([tex]x^{2} -1[/tex]) - ([tex]x^{2} -2x+3[/tex]) = [tex]x^{2} -1[/tex] - [tex]x^{2}[/tex] + 2x - 3 = 2x - 4
u(x)*w(x) = ([tex]x^{2} -1[/tex]) * ([tex]x^{2} -2x+3[/tex]) = [tex]x^{4}[/tex] - 2[tex]x^{3}[/tex] + 3[tex]x^{2}[/tex] - [tex]x^{2}[/tex] + 2x - 3 =
= [tex]x^{4} - 2x^{3}+2x^{2} +2x-3[/tex]
b) u(x)-w(x) = (2[tex]x^{2} -1[/tex]) - ( [tex]3x^{3} -x^{2}[/tex] ) = 2[tex]x^{2} -1[/tex] - [tex]3x^{3} +x^{2}[/tex] = - 3[tex]x^{3}[/tex] +3[tex]x^{2}[/tex] - 1
u(x)*w(x) = (2[tex]x^{2} -1[/tex]) * ( [tex]3x^{3} -x^{2}[/tex] ) = [tex]6x^{5} -2x^{4} -3x^{3} +x^{2}[/tex]
Szczegółowe wyjaśnienie:
Odpowiedź:
2.
a) u(x) = x² - 1, w(x) = x² - 2x + 3
u(x) - w(x) = x² - 1 - (x² - 2x + 3) = x² - 1 - x² + 2x - 3 = 2x - 4
u(x)•w(x) =
(x² - 1)•(x² - 2x + 3) = x⁴ - x² - 2x³ + 2x + 3x² - 3 = x⁴ - 2x³ + 2x² + 2x - 3
b) u(x) = 2x² - 1, w(x) = 3x³ - x²
u(x) - w(x) = 2x² - 1 - 3x³ + x² = - 3x³ + 3x² - 1
u(x)•w(x) = (2x² - 1)(3x³ - x²) = 6x⁵ - 3x³ - 2x⁴ + x²
Szczegółowe wyjaśnienie:
2.
a) u(x) = x² - 1, w(x) = x² - 2x + 3
u(x) - w(x) = x² - 1 - (x² - 2x + 3) = x² - 1 - x² + 2x - 3 = 2x - 4
u(x)•w(x) =
(x² - 1)•(x² - 2x + 3) = x⁴ - x² - 2x³ + 2x + 3x² - 3 = x⁴ - 2x³ + 2x² + 2x - 3
b) u(x) = 2x² - 1, w(x) = 3x³ - x²
u(x) - w(x) = 2x² - 1 - 3x³ + x² = - 3x³ + 3x² - 1
u(x)•w(x) = (2x² - 1)•(3x³ - x²) = 6x⁵ - 3x³ - 2x⁴ + x²